2006
DOI: 10.1262/jrd.17105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Freezability of Goat Spermatozoa Collected into Tubes Containing Extender Supplemented with Bovine Serum Albumin (BSA)

Abstract: Abstract. The purpose of this study was to investigate the effects of semen collection into tubes containing extender supplemented with BSA on the cryosurvival of goat spermatozoa. Semen was collected from two goats into empty tubes or tubes containing 10 ml extender supplemented with 0, 0.1, 1, or 5% BSA, and the washed spermatozoa were frozen as pellets in egg yolk-trehalose extender with the addition of 0.04% SDS and 4% glycerol. Sperm motion parameters were evaluated after postthawing and during a thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
2
3
0
3
Order By: Relevance
“…In cattle, BSA is found in reproductive tract fluids, and helps to preserve sperm motility and acrosome integrity during the semen freezing process (Yamashiro et al 2006). In the present study, GSH and GGSG had a slight promoting effect on sperm motility, while ROS increased.…”
Section: Discussionsupporting
confidence: 49%
“…In cattle, BSA is found in reproductive tract fluids, and helps to preserve sperm motility and acrosome integrity during the semen freezing process (Yamashiro et al 2006). In the present study, GSH and GGSG had a slight promoting effect on sperm motility, while ROS increased.…”
Section: Discussionsupporting
confidence: 49%
“…These studies showed that BSA significantly improved semen characteristics. BSA is found in reproductive tract fluids, and helps to preserve sperm motility and acrosomal integrity during the semen freezing process in goat [64]. Embryos from swine can be developed in vitro from the zygote to the blastocyst stage in a culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Kandungan BSA dalam CEP-2 merupakan makromolekul yang berperan mengikat ion Ca 2+ , mencegah masuknya ion Ca 2+ berlebihan ke sitosol, memungkinkan membran untuk lebih efektif dalam mengatur pergerakan ion Ca 2+ melewati membran dan menghambat akumulasi ion Ca 2+ intraseluler ke tingkat toksik bagi spermatozoa, sehingga viabilitas, motilitas dan jumlah spermatozoa belum terkapasitasi dapat dipertahankan tetap tinggi (Landim-Alvarenga et al, 2004). Yamashiro et al (2006) menjelaskan bahwa penambahan 5% BSA dalam pengencer Tris (hydroxymethyl-aminomethane)-citric acidglucose pada spermatozoakambing Shiba post-thawingmenghasilkan motilitas yang lebih tinggi (77,3+3,7)% dibandingkan dengan spermatozoa tanpa BSA (58,6+5,9)%. Penelitian Osman, et al (2012) melaporkan bahwa viabilitas spermatozoa sapi Piedmontese sebesar (38,743±0,854) % setelah penyimpanan pada suhu 4 o C selama 31 hari dengan level BSA 8 mg/ml.…”
Section: Pendahuluanunclassified